Successful Treatment of Pediatric Refractory Burkitt Lymphoma PTLD after Liver Transplantation using Anti-CD19 Chimeric Antigen Receptor T-Cell Therapy. (25th February 2021) - Wang, Tianyi; Feng, Mingxuan; Luo, Chengjuan; Wan, Xinyu; Pan, Ci; Tang, Jingyan; Xue, Feng; Yin, Minzhi; Lu, Dongqing; Xia, Qiang; Li, Benshang; Chen, Jing
In the immunocompromised setting, recipients of solid-organ or hematopoietic stem-cell transplants carry an increased risk of post-transplant lymphoproliferative disorder (PTLD). Burkitt lymphoma (BL) PTLD is a rare form of monomorphic B-cell PTLD, which lacks a standard best treatment. Here, we report the successful treatment of refractory BL-PTLD with autologous anti-CD19 chimeric antigen receptor (CAR) T-cell therapy. A male patient was diagnosed with BL-PTLD, with an increasing Epstein-Barr virus (EBV) viral load, at 21 months after undergoing living liver transplantation from his mother due to neonatal biliary atresia. After 10 cycles rituximab +/− intensive chemotherapy and surgical tumor resection, the tumors significantly advanced. Next-generation sequencing (NGS) was performed on formalin-fixed paraffin-embedded tumor tissue, revealing one mutation in exon 5, TP53: p.A159 V, which may be associated with chemo-resistance. Thus, treatment was started with autologous anti-CD19 CAR T-cell therapy. We administered 9.0 × 10 6 /kg autologous anti-CD19 CAR T-cells, after conditioning with cyclophosphamide and fludarabine. Unexpectedly, the patient experienced only mild (Grade II) cytokine release syndrome (CRS) without neurotoxicity. Finally, he went into complete remission (CR), and has achieved 16-month event-free survival to date. In addition, liver function has remained stably within the normal range without any immunosuppressive therapy. The literature includes only five previously reported BL cases treated with CAR T-cell therapy. In conclusion, the present case suggests that autologous anti-CD19 CAR T-cell therapy may represent a new therapeutic option for some cases of refractory BL-PTLD. Clinical trial number: ChiCTR2000032211.